Resultados de la recaudación del impuesto a las nóminas en el caribe mexicano: Gestión presidencial 2018 - 2019; Results of payroll tax collection in the Mexican Caribbean: Federal administration 2018-2019 - Sergio Lagunas Puls; Beatriz de la Trinidad Rocha Martínez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– Analysis has been made on whether the presidential administration of Mexico, which began in December 2018 with anti-neoliberal economic policies, has had an impact and to what extent whit respect to the collection of the payroll tax in the state of Quintana Roo and, as a contrast variable, the international passengers. The adjustment variable, identify the distribution in order to represent the magnitude of the changes. To find out if there is some independence from the government management, it s been realized independence test in different presidential terms. It is note that there were significant changes in the collection of the payroll test, however, the Independence test suggest that despite them where unrelated to the presidential management.
Keywords: H71; C16; E62; 330; Payroll tax; presidential administration; Quintana Roo; Mexico